Joint association of ultra-processed food and sedentary behavior with anxiety-induced sleep disturbance among Brazilian adolescents - Werneck, André O [UNESP] (2020)
Aims: We analyzed the joint association of high ultra-processed food ingestion and sedentary behavior (SB) with anxiety-induced sleep disturbance among Brazilian adolescents. Methods: Data from the Brazilian Scholar Health Survey, a nationally representative survey of 9th grade adolescents [mean: 14.28 years (range: 11–18 years)] conducted in 2015 (n = 100,648) were used. Self-reported anxiety-induced sleep disturbance, SB (TV viewing and total sitting time), and frequency of ingestion of different ultra-processed foods were collected. Age, ethnicity, type of city (capital or interior), region of the country, and habitual physical activity (global scholar survey questionnaire) were covariates. Logistic regression analyses were conducted to assess the associations. Results: High ultra-processed food ingestion plus low SB [boys:OR:1.44(99%CI:1.16–1.79), girls:OR:1.41(99%CI:1.22–1.63)] were risk factors for anxiety-induced sleep disturbance. The highest risk of anxiety-induced sleep disturbance was observed among those who joint high ultra-processed food ingestion with high SB [boys:OR:1.85(99%CI:1.46–2.35), girls:OR:1.62(99%CI:1.39–1.89)]. In addition, the interaction of high ultra-processed food ingestion with TV-viewing substantially increased the odds of anxiety-induced sleep disturbance [boys:OR:2.03(99%CI:1.61–2.56), girls:OR:2.04(99%CI:1.76–2.36)]. Conclusions: Both the high consumption of ultra-processed foods and SB (especially TV-viewing) appear to be independently associated with anxiety-induced sleep disturbance in both sexes. However, the co-occurrence of both negative lifestyle behaviors is associated with a substantial increase in the risk of anxiety-induced sleep disturbance. Future longitudinal research is required to confirm/refute our findings and explore potential mechanisms.